HUBUNGAN MOTIVASI BELAJAR DENGAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS XII SMK NEGERI 2 MERANGIN - Muhammad Jainuri; Sugeng Riyadi; Efit Feri Astanti (Pendidikan Matematika | STKIP YM Bangko, 2023)
The history of this studies is the low gaining knowledge of motivation and potential to assume creatively mathematically, primarily based on the consequences of the pre-check where there may be 1 tricky indicator, specifically 2 flexibility signs. The motive of this examine was to describe a large dating between studying motivation and the potential to assume creatively mathematically. This take a look at uses a quantitative approach with correlational methods. The populace on this study were all elegance XII students at SMK Negeri 2 Merangin inclusive of 6 instructions with 128 students. with the aid of the usage of the Slovin method, ninetyseven students were selected as samples. The sampling technique in this take a look at turned into simple random sampling by lottery. data series techniques in this study had been questionnaires and tests. The device used become within the shape of 41 declaration gadgets and three items about the potential to suppose creatively mathematically. based on the evaluation, the facts is commonly allotted and has a linear pattern. The information evaluation approach used to check the speculation is the pearson product moment, to test the significance the usage of the Z-test, followed by the figuring out coefficient formulation to specific the dimensions of the contribution of variable X to variable Y. based totally on statistics evaluation, it shows that the outcomes of the Pearson product second test are rcount > rtable or 0.238 > zero.198, the result of the Z-test is Zcount > Ztable or 2.332 > 1.960, followed with the aid of the result of the determinant coefficient test is five.sixty six%, then H0 is rejected and H1 is normal that means that there is a enormous dating among gaining knowledge of motivation and potential think creatively mathematically in elegance XII college students of SMK Negeri 2 Merangin for the 2022/2023 instructional yr